NEWER TECHNOLOGY FOR TUBERCULOSIS PREVENTION AND CARE IN RESOURCE-CONSTRAINED SETTINGS: PLANS AND UPCOMING GUIDANCE (Journal of Medical & Health Sciences Review, 2025)
Nowadays, one of the leading widespread communicable health determinants of death globally is tuberculosis (TB), which is most prevalent in low-and middle-income nations where health systems consistently struggle with a lack of diagnostic and therapeutic resources (World Health Organization 2024). To address these issues, more digital health solutions are used, such as digital adherence technologies (DATs), video-observed therapy (VOT), artificial intelligence (AI)-enabled chest X-ray computer-aided detection (CAD), electronic surveillance, laboratory connectivity, and mobile financial incentives (Cattamanchi et al., 2021). While solutions like digital adherence technologies (DATs) and video-observed therapy (VOT) significantly enhance patient accessibility and participation in tuberculosis prevention, their efficacy in improving treatment outcomes remains variable (Subbaraman et al., 2018). The World Health Organization (WHO) authorised CAD as a triage method for tuberculosis screening, as it is as precise as radiography (Qin et al., 2021). When used in African contexts, connectivity technologies such as GxAlert reduce the time between diagnosis and the start of therapy (SystemOne, 2020). Besides, socioeconomic barriers to adherence are addressed through mobile money-based incentives, which have been investigated in TB programs in Africa (Krishnan et al., 2021). Additionally, long-term effectiveness, equity, compatibility, and coordination and regulation of digital health technologies remain enduring issues (Wingfield et al., 2020). The analysis highlights crucial perspectives and insights from current research, demonstrating the primary role of digital health applications in tuberculosis prevention in facilitating patient-focused, comprehensive care, distinct from alternatives to fundamental TB services (World Health Organization, 2024).